MATEMATIKA VISUAL: MENUMBUHKAN PEMAHAMAN KONSEP MELALUI VIDEO EDUKATIF - Pattimukay, Nessy; Kempa, Evelin Martha (Universitas Pattimura, 2025)
Mathematics learning in elementary schools focuses on the development of conceptual understanding aimed at enhancing logical, analytical, and creative thinking skills, as well as their ability to solve real-life problems. Conceptual understanding of mathematics can be achieved through various approaches, one of which is the utilization of technology-based learning media, such as educational videos. The topics of Least Common Multiple (LCM) and Greatest Common Divisor (GCD) are among the essential materials taught in elementary schools that often cause difficulties for students in understanding and applying the concepts correctly. The community service activity aims to improve students’ understanding of mathematical concepts, particularly LCM and GCD, through the implementation of technology-based learning using educational videos. In addition, the activity seeks to foster students’ learning motivation and interest in mathematics and to provide teachers with innovative and engaging alternative teaching methods. The implementation method consists of three main stages: (1) preparation of learning media, including educational videos and student worksheets (LKPD), (2) classroom implementation at State Elementary School 283, Central Maluku Regency, where students watched the educational videos, worked in small groups of 4 -5 to complete the worksheets, and presented their results in front of the class, and (3) reflection, in which students provided written feedback on their learning experiences. The results indicate that the use of educational videos in mathematics learning effectively enhanced students’ understanding of LCM and GCD concepts, created a more interactive and enjoyable learning atmosphere, and increased students’ enthusiasm for learning. Teachers also benefited from the activity, as it provided a more engaging and effective teaching approach. Overall. The program successfully achieved its objectives and is expected to continue to further deepen students’ mathematical understanding and improve the quality of mathematics learning in elementary schools